Anti-inflammatory bowel effect of industrial orange by-products in DSS-treated mice. Issue 9 (31st August 2018) - Pacheco, M. Teresa; Vezza, Teresa; Diez-Echave, Patricia; Utrilla, Pilar; Villamiel, Mar; Moreno, F. Javier
Abstract : Pectin, phenolic compounds and/or Maillard reaction products present in orange by-products may exert an anti-inflammatory bowel effect in DSS-treated mice. Abstract : This work addresses the role of different by-products derived from the industrial extraction of orange juice in a possible anti-inflammatory effect in mice with colitis induced by dextran sulfate sodium (DSS). Fresh orange residue (FOR), dry orange residue (DOR), orange liqueur (OL) and animal feed (AF), as well as commercial citrus pectin (CP), were administered to C57BL/6J mice for 15 days before starting the DSS treatment. Analysis of macroscopic parameters such as the Disease Activity Index (DAI) and the colonic weight/length ratio revealed an anti-inflammatory effect following intake of FOR, AF or CP. Moreover, q-PCR of RNA from colonic tissue indicated measurable changes in the expression of TNF-α, IL-1β, iNOS, and intercellular adhesion molecules ICAM I, as well as in intestinal barrier proteins such as MUC-3, occludin, and ZO-1. Pectin, phenolic compounds and/or Maillard reaction products formed at initial steps were identified as relevant components exerting the ascribed beneficial effects. Our findings could open up the further application of a variety of orange by-products as food supplements in the potential amelioration of inflammatory bowel diseases.